Analisis Wacana Kritis Dalam Film Dokumenter “Dirty Vote” - Sukma Lestari , Rahmawati; Ahriani, Andi (Al-Hikmah: Jurnal Dakwah dan Komunikasi, 2025)
Film is a mass communication medium used as a means of entertainment, information, and also as a tool for conveying social and political messages to the public. Films come in many types, one of which is documentary films, which are based on the documentation of real events. The documentary film Dirty Vote represents the political situation in Indonesia during the 2024 General Election. The film Dirty Vote shows that various fraudulent practices were carried out by political elites in the 2024 election, ranging from the campaign period to the days leading up to voting day.The research method used in this study is qualitative, employing a literature study approach. This research is analyzed using Norman Fairclough’s critical discourse analysis model, which includes analysis of textual dimensions, discourse practices, and sociocultural practices. The results of the critical discourse analysis on this film indicate that there are five major themes of electoral fraud portrayed in the documentary, namely:First, the discourse surrounding President Jokowi’s inconsistent statements regarding Gibran’s candidacy. Second, the discourse on the creation of new administrative regions in Papua Island aimed at securing a first-round victory. Third, the discourse on maladministration by the President and the non-neutrality of state officials